Implementation of the Pentahelix Model Collaboration in Identifying the Tourism Potential of the Puncak Kabun Area, Agam Regency - Mandalia, Siska; Saputra, Ari; Wulandari, Wiranda (Universitas Pendidikan Indonesia, 2023)
ABSTRACTThe main problem is how collaboration is carried out by each stakeholder in identifying tourism potential in the Puncak Kabun area of Agam Regency. The purpose of this study is to determine whether stakeholders collaborate or not, in identifying tourism potential in the Puncak Kabun area. This study is field researchto obtain data on the problems studied. The data collection technique used is Snowball. Data processing was carried out in a qualitative and descriptive manner, to ensure the validity of the data, the researcher conducted member checks to find out how far the data obtained were in accordance with what was provided by the data provider. From the conducted field research there are seven components of collaboration that must be met by stakeholders, namely: Shared Understanding or Common Goals, Administration, Trust, Commitment, Mutuality, Communication, and Collaborative environment. However, in the Puncak Kabun area, the seven components of collaboration that must be carried out by stakeholders in identifying tourism potential that have not been implemented properly. Puncak Kabun area is an unofficial area and the business activities in it are still privately owned.ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui kerjasama atau tidaknya stakeholder dalam mengidentifikasi potensi wisata di kawasan Puncak Kabun. Ini adalah penelitian lapangan untuk mendapatkan data tentang masalah yang diteliti. Teknik pengumpulan data yang peneliti gunakan adalah Snowball. Pengolahan data dilakukan secara deskriptif kualitatif. Untuk memastikan keabsahan data, peneliti melakukan member check untuk mengetahui sejauh mana data yang diperoleh sesuai dengan apa yang diberikan oleh penyedia data. Dari penelitian yang peneliti lakukan di lapangan, tujuh komponen kerjasama yang harus dipenuhi oleh para pemangku kepentingan, yaitu: pemahaman bersama/ tujuan bersama, Administrasi, Kepercayaan, Komitmen, Kebersamaan, Komunikasi, dan Lingkungan kolaboratif. Namun di kawasan Puncak Kabun, tujuh komponen kolaborasi yang harus dilakukan pemangku kepentingan dalam mengidentifikasi potensi wisata belum terlaksana dengan baik. Pasalnya, kawasan Puncak Kabun merupakan kawasan tidak resmi, dan kegiatan bisnis di dalamnya masih dimiliki oleh swasta.